Teoría Fundada Arte o Ciencia - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2009)
Abstract. The article is addressed to social researchers who are interested in inductive building theory, through the qualitative analysis of data. It presents the main features of the grounded theory: its origins, similarities with other social research strategies, a brief conceptualization and the most important methodological orientations (constant comparative method and theoretical sampling). It also provides an overview of the techniques for collecting and registering data. Finally, the article points out the limits and possibilities of the grounded theory in social research. Resumen. El artículo se refiere a los investigadores sociales que están interesados en teoría inductiva del dato, con el análisis cualitativo de datos. Presenta las características principales de la teoría puesta a tierra: sus orígenes, semejanzas con otras estrategias sociales de la investigación, una breve conceptualización y las orientaciones metodológicas más importantes (método comparativo constante y muestreo teórico). También proporciona una descripción de las técnicas para recoger y colocar datos. Finalmente, el artículo precisa los límites y las posibilidades de la teoría puesta a tierra en la investigación social